Montessori Method to Improve Writing Skill in Seventh Grade Students at Otavalo School - Tabango Vallejos, Holly Mishell (2024)
Propose strategies focused on didactic material based on the Montessori method to improve the writing skills of seventh grade students of the "Otavalo" school.